2017
DOI: 10.1111/andr.12341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of icariin in combination with daily sildenafil on penile atrophy and erectile dysfunction in a rat model of bilateral cavernous nerves injury

Abstract: The commonly utilized phosphodiesterase type 5 inhibitors do not lead to satisfactory penile erection after radical prostatectomy mainly because of insufficient nitric oxide drive from the damaged cavernous nerves. The aim of this study was to assess the efficacy and mechanisms of icariin in combination with daily sildenafil on neurogenic erectile dysfunction and penile atrophy in a rat model of bilateral cavernous nerves injury. Sixty male Sprague-Dawley rats injected with 5-ethynyl-2-deoxyuridine (50 mg/kg) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
10
0
1
Order By: Relevance
“…In this study, for our ICP experiment, we assessed related parameters, such as maximum ICP, the maximum ICP/MAP ratio, and the slope of maximum ICP, 3 weeks after the modelling operation and showed that the administration of either salidroside or rapamycin can ameliorate ED in rats suffering from BCNI. CN‐injured ED leads to atrophy due to long‐term hypoxia and fibrotic deposition (Xu et al., 2017), and the penile tissue weight/body weight ratio in the M group was similar to the previous results. Meanwhile, results indicated that both salidroside and rapamycin treatment maintained the penile index and the area of the CC compared to those in the M group.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, for our ICP experiment, we assessed related parameters, such as maximum ICP, the maximum ICP/MAP ratio, and the slope of maximum ICP, 3 weeks after the modelling operation and showed that the administration of either salidroside or rapamycin can ameliorate ED in rats suffering from BCNI. CN‐injured ED leads to atrophy due to long‐term hypoxia and fibrotic deposition (Xu et al., 2017), and the penile tissue weight/body weight ratio in the M group was similar to the previous results. Meanwhile, results indicated that both salidroside and rapamycin treatment maintained the penile index and the area of the CC compared to those in the M group.…”
Section: Discussionsupporting
confidence: 86%
“…Twelve SD rats were randomly assigned to the sham group (i.e., exposing and isolating CNs, without crushing CNs) and received an ICI of 0.2 ml phosphate buffer solution (PBS). In the other 120 rats, the CNs were isolated and crushed bilaterally using a microsurgical needle holder [18]. On the same day of surgery, the rats that underwent bilateral CNs injury were randomly divided into three groups: those who received an ICI of 0.2 ml PBS (n = 24 animals), free ADSCs suspension (abbreviated to FAs, 0.5 £ 10 6 , 1 £ 10 6 , 2 £ 10 6 and 4 £ 10 6 cells in 0.2 ml PBS, n = 12 animals per dose), or ADSCs-based spheroids (abbreviated to ASs, 500, 1000, 2000 and 4000 ASs in 0.2 ml PBS, 1 £ 10 3 ADSCs per spheroid, n = 12 animals per group).…”
Section: Experimental Designmentioning
confidence: 99%
“…Sıçan penis dokusunda reaktif oksijen türlerinin (ROS) aşırı üretiminin erektil disfonksiyon gelişiminde önemli bir rol oynadığı gösterilmiştir (28,29). Süperoksit anyonu hızla NO'yu inaktive eder, kavernozal düz kasları gevşetme yeteneğini bozar (30) (39). Özden ve arkadaşlarının yaptığı bir çalışmada da unilateral ve bilateral kavernöz sinir hasarı yapılan sıçanlarda sildenafil tedavisinin penil ağırlık üzerine olumlu etkileri olduğu görülmüş, TUNEL ile düz kaslarda apoptoza giden hücre sayısında bilateral sinir hasarı yapılan grupta artış olduğu ve sildenafil uygulamasının apoptozu önleme yönünde olumlu etkileri olduğu ortaya konmuştur (40).…”
Section: İmmünohistokimyasal Boyama Yöntemiunclassified